Uso de aeronaves remotamente pilotadas (ARP) e geotecnologias no zoneamento edáfico em sistema silvipastoril - Ribeiro Filho, Reinaldo Baldotto (2023)
Performing chemical analyzes on soils and associating them with the morphological characteristics of the species that make up a productive silvipastoral system is one of the main tools for planning and managing this activity. Thus, this research had as main objective to map the spatial distribution of nutrients in the soil, in a 5-year silvipastoral system with brachiaria-brizantha (Urochloa brizantha) and jacaranda-da-bahia (Dalbergia nigra) and investigate their effect and the correlation between the morphological characteristics of these two species that make up this consortium. The work was carried out in the district of Pacotuba, Cachoeiro de Itapemirim, ES, in an experimental area of the Capixaba Institute for Research, Technical Assistance and Rural Extension (INCAPER). With the data made available in the geographic information systems environment, the working area was delimited, encompassing the cultivated area, with the purpose of serving as a basis for the creation of a regular mesh of points, which allowed the systematic sampling of soils, of trees (height and circumference) and brachiaria (leaf area, number of tillers, width and length of leaves). This procedure was carried out by collecting information on an 18 by 18 m grid that totaled 75 sampling points with known coordinates. For soil sampling, deformed samples were collected at depths of 0-10 cm in order to obtain quantitative data on soil nutrients. From high spatial resolution images obtained using remotely piloted aircraft (ARP), nutrient data from soil, pasture, forest inventory and sample plots were superimposed to assist in comparative analysis, and allowed the identification of areas with less canopy development, mainly in the northeastern portion of the area. By crossing spatialized data on soil nutrients, forest inventory and pasture sampling with data obtained using ARP, it was possible to correlate them with regard to the lesser or greater development of the system. It was also possible to analyze whether the quality of the soil influenced the diameter and height of the Bahia rosewood, as well as the leaf area, size and width of the brachiaria tillers. In this way, the use of remotely piloted aircraft, together with a georeferenced database, proved to be a powerful innovative tool to support decision-making, allowing the main areas that require additional care to be identified